Dermatoscopy - Pietkiewicz, Paweł (IntechOpen, 2022)
This book is a collection of chapters on dermatoscopy, which is a fast, easy-to-learn, low-cost, and non-invasive diagnostic method utilizing the Rayleigh scattering phenomenon to visualize epidermal and subepidermal structures. Dermatoscopy has become increasingly popular for allowing visualization of structures that are impossible to see with the naked eye. Its use provides insight into the biological potential of skin lesions, enabling efficient management and follow-up. The book focuses on the features of some of the most common skin neoplasms, such as combined nevi, as well as those that are more challenging to assess, such as pigmented lesions of the eyelid margins. It also provides novel insights into the role of dermatoscopy in palmoplantar dermatoses and discusses precautions in dermatoscopy during the SARS-CoV2 pandemic.